A critical edition of the poems of Henry Vaux (c. 1559-1587) in MS. Folger Bd with STC 22957 - Hacksley, Timothy Christopher (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2008)
This thesis offers an edition of the English and Latin poems found in MS. Folger bd with STC 22957, attributed to Henry Vaux (c. 1559"”1587), a recusant, priest-smuggler, and child prodigy. THE TEXT of the edition is preceded by an introduction comprising three parts: a GENERAL INTRODUCTION describing Vaux's socio-historical and biographical context; a CRITICAL INTRODUCTION describing the Medieval and Early Modern literary contexts of Vaux's poems and the forms, traditions, topoi, and conventions adhered to in them; and a TEXTUAL INTRODUCTION describing the seventeenth-century manuscript copy of the poems used as the source text and explaining and justifying the editorial decisions made. Textual variants and instances of doubtful authorship are also discussed. THE TEXT itself is presented in the original spelling of the MS. and is a diplomatic edition: the scribe's use of characters that are now defunct (such as long "—s' and "—=' for "—-') has not been modernised. A critical apparatus is provided with THE TEXT. THE TEXT is followed by an extensive COMMENTARY, which glosses un-usual or archaic words and phrases, points out allusions and their likely sources, discusses literary forms and conventions which inform the reading of the po-ems, and observes peculiarities in poetic metre. Translations and commentary are offered for Vaux's Latin poems. The five appendices following the COMMEN-TARY comprise a MODERNISED TEXT of the poems, a FACSIMILE OF THE FOLGER MS., a SUBSEQUENT HISTORY OF THE VAUX FAMILY after Henry Vaux's death, a text JOHN OF PECHAM'S PHILOMENA PRAEVIA (a text which informs the reading of Vaux's "•A complaint to the Nightingale"–) along with a parallel translation by me, and transcriptions of TEXTUAL VARIANTS. A BIBLIOGRAPHY of works cited, re-ferred to or consulted follows the appendices. A comprehensive GENERAL INDEX of subjects, people, places, and literary works and forms follows this, and an IN-DEX OF FIRST LINES AND TITLES of Vaux's poems completes the edition.
Keywords: Vaux, Henry, ca. 1559-1587 -- Criticism and interpretation; Vaux, Henry, ca. 1559-1587; Latin poetry, Medieval and modern -- History and criticism; English poetry -- Early modern, 1500-1700